An Analisis Buku Teks Bahasa Inggris untuk Siswa Kelas IV Sekolah Dasar - Edo Nugraha, Adiyanto; Karlina Ambarwati, Evi (English Education:Journal of English Teaching and Research, 2023)
The purpose of this study was to determine if the English textbook My Next Words for the fourth grade was acceptable for English Language Teaching based on the Badan Standar Nasional Pendidikan (BSNP). The study employed descriptive qualitative research with document or content analysis. The research material was derived from My Next Words, an English textbook for Grade 4 elementary school students in Indonesia. The textbook was analyzed in terms of materials, language features, and graphic under the list of content requested by BSNP 2022. According to the findings, the My Next Words textbook for a fourth grade was categorized as good and acceptable according to the BSNP 2022 criterion. Grammar and spelling in the textbook, on the other hand, require greater attention. Equally important, various cultures must be covered in the textbook.